The Metaphysics Of Gender Identity: Between Essentialism And Social Constructivism - Muhammad Amin; Ahmad (PT. Gudang Pustaka Cendekia, 2025)
This article examines gender identity within a metaphysical framework by exploring the tension between essentialist and social constructivist paradigms. The core issue addressed in this research is the absence of a conceptual framework capable of reconciling these two traditionally opposing approaches. Essentialism regards gender as a fixed, inherent attribute, whereas constructivism emphasizes that gender is shaped by social and cultural practices. The aim of this study is to formulate a hybrid metaphysical model that integrates both perspectives through dialectical synthesis. The methodology employed involves a philosophical literature review with thematic analysis of works published within the last five years. Findings reveal that a relationally grounded hybrid model successfully merges the strengths of both paradigms, offering a more inclusive and applicable approach for social policy development. This model is viewed as critical for advancing academic discourse while also providing a robust philosophical foundation for the recognition and protection of gender diversity in contemporary society.